Care to patient in heart arrest at the intensive care unit - Luiza Taciana Rodrigues de Moura; Lusineide Carmo Andrade de Lacerda; Danielle Dionísio Santos Gonçalves; Roxana Braga de Andrade; Yanne Ramos de Oliveira (Rev Rene)
Care to heart arrest patient should be performed in a systematic way, based on basic protocol as well as advanced life support. The objective of this study is to assess the knowledge of the nursing staff of an intensive care unit in relation to the recognition of heart arrest and the establishment of resuscitation according to the protocols above. It is a descriptive and quantitative study which was conducted from April to June 2011. Of the 33 professionals who participated in the study, 54.5% had not undergone previous training on the theme, 93.9% partially agreed the rates of heart arrest, and only 15.2 % got all the maneuvers in ventilating intubated patient. The low hit total demonstrates the need to update the nursing staff, with periodical theoretical-practical training, and systematic assessments of the performance of the team.